2013 American Control Conference 2013
DOI: 10.1109/acc.2013.6580917
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of coupled nonlinear oscillators with shifted gamma-distributed delays

Abstract: Abstract-We derive conditions for the synchronization of coupled nonlinear oscillators affected by distributed delays in the interconnections. The distributed delays are characterized by a gamma-distribution kernel with a gap. The approach is based on the stability analysis of synchronized equilibria in the (delays,gain) parameter space and the characterization of the structure of the emanating solutions at the bifurcations. The results are applied to networks of coupled Lorenz system. In particular it is show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
0
10
0
1
Order By: Relevance
“…It is important to recall that, in a neighborhood of the origin, the stability of the solution of the normal form (20) in the center manifold proves the local stability of the solution of the initial infinite dimensional system (11). Moreover, one can easily establish values for α, β and γ so that the matrix associated with the linear part of the normal form (20) be Hurwitz (all eigenvalues with negative real part).…”
Section: Concluding Remarkmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to recall that, in a neighborhood of the origin, the stability of the solution of the normal form (20) in the center manifold proves the local stability of the solution of the initial infinite dimensional system (11). Moreover, one can easily establish values for α, β and γ so that the matrix associated with the linear part of the normal form (20) be Hurwitz (all eigenvalues with negative real part).…”
Section: Concluding Remarkmentioning
confidence: 99%
“…Indeed, the behavior of a system (even a linear one) may be different from the behavior of its approximation. In [11], it has been shown that using a polynomial function (1 − s τ n ) n of arbitrary degree n to approximate an exponential e −sτ allows finding stabilizing controller gains for the approximated system even when they do not necessarily exist for the original one. Furthermore, introducing a deliberately delay was suggested in [12] to solve the static output feedback sliding mode control problem for a broader class of linear uncertain systems.…”
Section: Introductionmentioning
confidence: 99%
“…The aim is to characterize the occurrence of synchronous behavior as a function of the parameters of the distributed delay. Preliminary results have been reported in . Here, we are going further by emphasizing the delay distribution effect on stability of the linearized system as well as the information we can get for the nonlinear one.…”
Section: Introductionmentioning
confidence: 94%
“…I.-C. MORȂRESCU, W. MICHIELS AND M. JUNGERS in [14]. Here, we are going further by emphasizing the delay distribution effect on stability of the linearized system as well as the information we can get for the nonlinear one.…”
mentioning
confidence: 96%
“…Consensus and synchronization are challenging problems widely studied in the context of linear agents interacting through a directed or undirected graph with a fixed or dynamically changing topology. There are also contributions related to nonlinear agents such as oscillators dynamics [4], nonholonomic robots [1] or general nonlinear systems [5].…”
Section: Introductionmentioning
confidence: 99%